BUILDING STUDENTS' AWARENESS OF GREEN BEHAVIOR THROUGH HEALTHY SNACK CHOICES IN ELEMENTARY SCHOOLS - apip rudianto; Nana Supriatna (Al-Aulad: Journal of Islamic Primary Education, 2025)
This study was motivated by an extraordinary event, namely the large number of students who experienced food poisoning after consuming snacks sold in the school environment. One of the causes of this event was the low level of students' understanding of green behavior in maintaining health, which was applied in their snacking behavior in the school environment. Students prefer to buy snacks they like rather than considering the healthiness of the snacks. This can impact future sustainability (sustainable development). This study aims to determine the extent of students' green behavior as seen in their snacking behavior. This study is a qualitative research. Data collection techniques include observation, interviews, and documentation. The data analysis technique used in this study is triangulation. Through triangulation, conclusions can be drawn regarding the attitude toward green behavior in choosing healthy snacks based on students' snacking behavior. The results of this study indicate that most students do not yet exhibit green behavior. This can be seen from the fact that students prefer to choose snacks based on their preferences and food trends rather than health or nutritional aspects. Students also have a low understanding of healthy snacks and are becoming more consumptive.